From crime anxiety to climate fear (Academic Journal of Internal Affairs, 2021)
Climate change and the extreme weather circumstances resulting from it, have accompanied the humanity’s history from its beginning. Actual communication related to global warming – mainly the prognosis of expected consequences – may cause anxiety or fear for a large group of people. The social effects resulting from it are considerable, they can even be serious insome cases. Nature and appearance of these phenomena can cause signs identifiable with criminal fear and anxiety. Instead of climate panic, time of climate action has to come now. After defining „ecological footprint” it is time for rediscovering „ecological handprint”. Treatment of both global and local problems is the duty of law enforcement organisations, which can be able to handle the consequences successfully and prepare the population for professional prevention.
Keywords: climate change; extreme weather; criminal fear and anxiety; climate fear